COVID-19 in complex common variable immunodeficiency patients affected by lung diseases. Issue 6 (December 2021) - Milito, Cinzia; Soccodato, Valentina; Auria, Stefania; Pulvirenti, Federica; Quinti, Isabella
Abstract : Purpose of review: In the general population, the risk of severe COVID-19 is associated with old age, male sex, hypertension, obesity and chronic diseases. Chronic lung diseases are listed as additional risk factors for hospitalization and ICU admission. The purpose of this review is to define whether chronic lung diseases, such as bronchiectasis and interstitial diseases, represent a risk for a severe SARS-CoV-2 infection in patients affected by common variable immunodeficiency (CVID), the most common symptomatic primary antibody defect. Recent findings: CVID patients with SARS-CoV-2 infection have been reported since the beginning of the pandemic with a wide range of clinical presentations ranging from asymptomatic to mild/moderate and severe COVID-19. The meta-analysis of 88 CVID cases described in large cohorts and case reports demonstrated that CVID patients with chronic lung involvement have an increased risk for severe COVID-19 in comparison to CVID without lung diseases (50 vs. 28%, relative risk 1.75, 95% confidence interval 1.04–2.92, P = 0.043). Differently from the general population, age and metabolic comorbidities did not represent a risk factor for severe course in this patient's population. Summary: Underlying chronic lung diseases but not age represent a risk factor for severe COVID-19 in CVID. Prompt therapeutic intervention should be adopted in SARS-CoV-2 positive CVID patients with chronic lung diseases independently of their age.